IMPACT OF DIGITAL TRANSFORMATION ON MECHANISMS OF STATE MANAGEMENT OF REGIONAL DEVELOPMENT - KORNAHA, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In the article, the impact of digital transformation on the mechanisms of state governance in regional development is explored. Conducting an analysis of current trends in the use of digital technologies in public administration, the authors examine the role of e-governance, big data, automation, and other digital tools in enhancing strategies and mechanisms to promote regional development. The article specifically emphasizes decentralization and the promotion of interaction among different levels of governance as key components for the successful implementation of digital strategies in the context of regional development. The conclusions of the article underscore the necessity of adapting state governance to the challenges of the digital era and the development of open and resilient mechanisms to support regional growth in the conditions of digital transformation. The article also focuses on cultural and educational transformations in the field of public administration, highlighting the significance of training and preparing personnel to work with modern digital tools. The cultural shift and improvement of digital literacy emerge as crucial elements for the successful implementation of digital technologies in state governance.Therefore, the article systematically categorizes and analyzes the impact of digital transformation on the mechanisms of state governance in regional development, taking into account key technological and organizational transformations that define the contemporary landscape of regional governance in the era of digital development.
Keywords: state governance; digital transformation; mechanism; regional development; business